Development, characterization, and in vivo assessment of mucoadhesive nanoparticles containing fluconazole for the local treatment of oral candidiasis - Rençber S (Dove Medical Press, 2016)
Seda Rençber,1 Sinem Yaprak Karavana,1 Fethiye Ferda Yilmaz,2 Bayri Eraç,2 Merve Nenni,3 Seda Özbal,4 Çetin Pekçetin,4 Hande Gurer-Orhan,3 Mine Hoşgör Limoncu,2 Pelin Güneri,5 Gökhan Ertan11Faculty of Pharmacy, Department of Pharmaceutical Technology, 2Department of Pharmaceutical Microbiology, 3Department of Pharmaceutical Toxicology, Ege University, Bornova, Turkey; 4Department of Histology and Embryology, School of Medicine, Dokuz Eylul University, Inciralti, Turkey; 5Faculty of Dentistry, Department of Oral Diagnosis and Radiology, Ege University, Bornova, TurkeyAbstract: This study aimed to develop a suitable buccal mucoadhesive nanoparticle (NP) formulation containing fluconazole for the local treatment of oral candidiasis. The suitability of the prepared formulations was assessed by means of particle size (PS), polydispersity index, and zeta potential measurements, morphology analysis, mucoadhesion studies, drug entrapment efficiency (EE), in vitro drug release, and stability studies. Based on the optimum NP formulation, ex vivo drug diffusion and in vitro cytotoxicity studies were performed. Besides, evaluation of the antifungal effect of the optimum formulation was evaluated using agar diffusion method, fungicidal activity-related in vitro release study, and time-dependent fungicidal activity. The effect of the optimum NP formulation on the healing of oral candidiasis was investigated in an animal model, which was employed for the first time in this study. The zeta potential, mucoadhesion, and in vitro drug release studies of various NP formulations revealed that chitosan-coated NP formulation containing EUDRAGIT® RS 2.5% had superior properties than other formulations. Concerning the stability study of the selected formulation, the formulation was found to be stable for 6 months. During the ex vivo drug diffusion study, no drug was found in receptor phase, and this is an indication of local effect. The in vitro antifungal activity studies showed the in vitro efficacy of the NP against Candida albicans for an extended period. Also, the formulation had no cytotoxic effect at the tested concentration. For the in vivo experiments, infected rabbits were successfully treated with local administration of the optimum NP formulation once a day. This study has shown that the mucoadhesive NP formulation containing fluconazole is a promising candidate with once-a-day application for the local treatment of oral candidiasis.Keywords: mucoadhesive nanoparticle, buccal application, oral candidiasis, fluconazole, chitosan